Environment-Friendly Control of Cucumber Downy Mildew Using Chlorine Dioxide - Byung-Ryun Kim; Soo-Sang Hahm; Mi-Kyung Kwon; Yun-Jeong Kim; Woon-Seop Kim; Jeong-Young Song; Sang-Keun Oh; Jung-Il Ju (Research in Plant Disease, 2021)
Pseudoperonospora cubensis (downy mildew) is highly virulent to various Cucurbitaceae crops, including cucumber (Cucumis sativus). We tested chlorine dioxide application in a plastic greenhouse for environmentfriendly control of downy mildew disease. Spraying diluted chlorine dioxide suppressed downy mildew disease with 41.2% control efficacy. Thermal fogging with chlorine dioxide had a high control efficacy of 80.9%, confirming that this approach is useful for environment-friendly downy mildew control. Using thermal fogging to control diseases that are greatly affected by humidity, such as downy mildew, may be more effective compared with conventional dilution spray control methods.